Preliminary Wind Analysis of Multistory Bents - Ben-Arroyo, Abraham (Engineering Journal, 1970)
Recent progress in computers has permitted rapid analysis of the multistory bent, including deformations due to horizontal forces. The first part of this paper presents an analysis of the girder and column forces and moments for an arbitrary story. Equilibrium equations are derived in general form, in terms of the external forces and bent geometry—an especially convenient approach for tabular work. The second part deals with the deformation of the multistory bent. An outline of the basic assumptions is followed by a proposed deformation curve, which yields the allowable deformation angle for any story, based on the allowable deflection index (drift limitation). Subsequently, equations are derived for the horizontal deflections due to each of the following factors: axial deformation of the columns, bending of the columns, and bending of the girders. The paper concludes with a numerical example.